2020
DOI: 10.21203/rs.2.20231/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Community–Based System Dynamics Approach for Understanding Factors Affecting Mental Health and Health Seeking Behaviors in Beirut and Beqaa Regions of Lebanon

Abstract: Background Available evidence on mental health and psychosocial problems in Lebanon is limited. Recent quantitative data suggests a high prevalence among Syrian refugees and their Lebanese host communities, with significant treatment gaps in both populations. This study aims to determine how Lebanese host and Syrian refugee communities perceive mental health, and identify health seeking behaviors and barriers to health access in two contrasting contexts of fragility.Methods A comparative qualitative study desi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…In response to the Syrian crisis, the MoPH in collaboration with the Ministry of Social Affairs and with local and international non-governmental organizations (NGOs) have been providing free-of-charge primary healthcare services, including mental health services, for UNHCR-registered Syrian refugees. Yet, due to limited nancial capacities, these efforts have been reportedly unable to meet the increasing needs of these vulnerable populations (46,47). The situation is even worse for unregistered refugees who have restricted capacities to receive the appropriate healthcare support (47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to the Syrian crisis, the MoPH in collaboration with the Ministry of Social Affairs and with local and international non-governmental organizations (NGOs) have been providing free-of-charge primary healthcare services, including mental health services, for UNHCR-registered Syrian refugees. Yet, due to limited nancial capacities, these efforts have been reportedly unable to meet the increasing needs of these vulnerable populations (46,47). The situation is even worse for unregistered refugees who have restricted capacities to receive the appropriate healthcare support (47).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that mental health services are not reaching enough refugees. Notwithstanding the value of the provided services, Syrian refugees cite many barriers to seeking mental health services in Lebanon, including lack of trust in and limited knowledge of available services, limited mental health literacy and perceived need for treatment, lack of services especially in rural areas, associated di culties in commuting, nancial barriers and lack of mental health coverage, and social stigma which may impede refugees seeking healthcare fearing of shame and discrimination (46). Furthermore, due to pervasive cultural beliefs, Syrian refugees tend to seek religious healers as a rst line of treatment for mental illness given their perceived cultural appropriateness and their reduced association with social stigma when compared to mental health professionals (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of a larger project which aimed to examine the dynamics of mental health and psychosocial support from the perspective of both health care professionals and Syrian refugee and Lebanese host community members in Beirut and Beqaa, Lebanon. A detailed account of the methods, including analogous workshops and interviews with community members, and ndings of said study can be found in Noubani et al (10). We comment on the triangulation of ndings against those of this latter study throughout the presentation of results.…”
Section: Triangulation Of Ndingsmentioning
confidence: 92%
“…This treatment gap may be due to several factors. Recent studies focused on the help-and health-seeking behaviours of individuals suffering from mental and psychosocial issues highlighted that utilization of health services is shaped by high social stigma and treatment costs, limited trust in public health systems and concerns over compromised con dentiality (10)(11)(12).…”
Section: Mental Health In Lebanonmentioning
confidence: 99%